Transformasi Pembelajaran Motorik Kasar melalui Sintesis Demonstrasi Gerak-Lagu dan Model ATIK: Studi di TK Pertiwi Saleppa - St. Maria Ulfah (Institut Agama Islam Negeri Madura, 2025)
The development of gross motor skills serves as a key aspect in early childhood education. This study aims to analyze the transformation of gross motor learning through the synthesis of movement-song demonstration and ATIK model at TK Pertiwi Saleppa. This qualitative research employs a case study design involving 20 group B students (5 males, 15 females) and their teachers as research subjects. Data collection utilizes participatory observation, in-depth interviews, and documentation. Research findings reveal three major improvements: First, teaching practices become more structured through systematic planning, interactive delivery, and comprehensive assessment. Second, student engagement increases, shown by enhanced cognitive involvement during observation and imitation phases, optimal physical participation during improvisation and creation stages, and growing social interaction throughout learning activities. Third, gross motor skills develop progressively, evidenced by improved movement coordination, better balance control, and expanded movement creativity. The synthesis of movement-song demonstration and ATIK model creates an effective framework for gross motor development while maintaining student engagement throughout the learning process.